2010
DOI: 10.1007/s12640-010-9196-9
|View full text |Cite
|
Sign up to set email alerts
|

Apathy in Neuropsychiatric Disease: Diagnosis, Pathophysiology, and Treatment

Abstract: Apathy is an increasingly recognized concomitant of a broad range of central nervous system disorders. Nevertheless, its nosology, pathogenesis and therapy remain shrouded in confusion and controversy. As yet, there is little consensus regarding methods for detecting apathy, or distinguishing it from depression, or for assessing its severity. Many now regard the apathy syndrome as primarily reflecting a lack of motivation that compromises emotional, cognitive, and overt behavioral function. Even though under-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
66
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(75 citation statements)
references
References 149 publications
(177 reference statements)
1
66
0
3
Order By: Relevance
“…Apathy is defined by decreased motivation towards goal-directed behaviours,1 and occurs as a symptom of a variety of different psychiatric and neurodegenerative diseases 2 3. Studies have shown that apathy occurs in 30–60% of patients with amyotrophic lateral sclerosis (ALS), and is the most prominent behavioural symptom of the disease 4–7.…”
Section: Introductionmentioning
confidence: 99%
“…Apathy is defined by decreased motivation towards goal-directed behaviours,1 and occurs as a symptom of a variety of different psychiatric and neurodegenerative diseases 2 3. Studies have shown that apathy occurs in 30–60% of patients with amyotrophic lateral sclerosis (ALS), and is the most prominent behavioural symptom of the disease 4–7.…”
Section: Introductionmentioning
confidence: 99%
“…Apathy is common in depression, affecting more than 30% of individuals with major depression, and is most prevalent in depressed older adults (Chase, 2011, Forsell et al, 1993, Krishnan et al, 1995, Lampe and Heeren, 2004, Mehta et al, 2008). The syndrome of apathy is defined as a primary motivational impairment that in depression results in diminished goal-oriented behavior, lack of intellectual interest, and indifference or flattening of affect (Marin, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The syndrome of apathy is defined as a primary motivational impairment that in depression results in diminished goal-oriented behavior, lack of intellectual interest, and indifference or flattening of affect (Marin, 1990). These clinical signs translate into apathetic, depressed patients being poorly engaged in treatment, posing a greater burden to caregivers, and having increased risk of future functional and cognitive impairment (Chase, 2011, Feil et al, 2003, Holtta et al, 2012). In geriatric depression, apathy predicts poor response of depressive symptoms to treatment, chronicity of depression, and disability (Chaturvedi and Sarmukaddam, 1986, Lavretsky et al, 1999, Levkovitz et al, 2011, Marin et al, 2003, Yeager and Hyer, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…At present, no pharmacological therapy is approved for the treatment of apathy [8]; however, the aforementioned possible roles of the dopaminergic system and the prefrontal cortex suggest that the modulation of the dopaminergic mesocortical pathway could represent a reasonable target to try to improve this disabling symptom in subjects with bv-FTD [9]. …”
Section: Introductionmentioning
confidence: 99%